An octopus is amazing - Lauber, Patricia; Keller, Holly (New York : HarperCollins, 1990)
An introduction to one of the curiosities of the sea--the multi-tentacled, highly intelligent octopus.
Elem. School Library Collection
School Library Journal
Wilson's Children
3.4
K-3.
K-3
Keywords: Octopuses -- Juvenile literature; Octopuses; Octopuses